An Object Lesson: Objects, Non-Objects, and the Power of Conceptual Construal in Adjective Extension. Issue 3 (3rd July 2021) - LaTourrette, Alexander; Waxman, Sandra R.
ABSTRACT: Despite the seemingly simple mapping between adjectives and perceptual properties (e.g., color, texture), preschool children have difficulty establishing the appropriate extension of novel adjectives. When children hear a novel adjective applied to an individual object, they successfully extend the adjective to other members of the same object category but have difficulty extending it more broadly to members of different categories. We propose that the source of this difficulty lies at the interface of the linguistic and conceptual systems: children initially limit the extension of an adjective to the category of the object on which it was introduced. To test this hypothesis, we manipulated whether participants construed images as "pictures of things" (objects) or "blobs of stuff" (non-objects). For both 36-month-old children (Experiments 1 and 2) and adults (Experiment 3), the conceptual status of an image influenced how they extended an adjective applied to that image. Children extended novel adjectives more successfully when they construed the images as non-objects than when they construed the same images as objects. Similarly, adults were faster to make adjective extensions when construing the images as non-objects rather than objects. Learners of all ages must navigate this linguistic-conceptual interface in assessing whether and how novel adjectives should be extended to new individuals.